Identifying information literacy skills of new graduate students - Nuryaman, Nuryaman; Rifai, Agus (Universitas Padjadjaran, 2024)
The UIN Syarif Hidayatullah Jakarta Graduate School Library organizes an information literacy program to create new students who are proficient in dealing with academic tasks. Understanding students' initial information literacy skills needs to be considered because it is input for developing information literacy programs that are more oriented toward student needs. This study aimed to identify the initial information literacy skills of new graduate students based on the Big6 Model. The research approach was quantitative with survey methods. A sample of 43 respondents was taken from a total population of 160 people using incidental techniques, namely students who were present in person at the 2022 Odd Semester New Student Orientation. Data was collected using a closed questionnaire with a Likert Scale. Data analysis and interpretation used descriptive statistics. The research results showed that the information literacy skills of new students were 70%, categorized as good. Students were confirmed to have evaluated search results at 74% while seeking strategies, and the use of information was at 68% and 69 (sufficient category). The condition of task definition and synthesis skills was 71%, location and access were 70%, with Google Scholar, Academia, and Moraref as the most frequently referenced sources of digital information; all three aspects were categorized as good. The preparation of search strategies and utilization of information sources is in the sufficient category. Therefore, these two aptitudes are considered to be the focus of academic library information literacy training in the future.